Prevalence of periapical abscesses in patients with systemic lupus erythematosus. (8th July 2021) - Rotstein, Ilan; Katz, Joseph
Abstract: Aims: To assess the prevalence of periapical abscesses in patients with systemic lupus erythematosus (SLE), and to evaluate the effect of glucocorticoids (GCs) used to treat SLE, on the prevalence of such lesions. Methods: Integrated data of hospital patients was used. Data from the corresponding diagnosis codes for SLE and periapical abscess was retrieved by searching the appropriate query in the database. The odd ratio (OR) of periapical abscesses and its association with SLE and intake of GCs were calculated and analyzed statistically. Results: The prevalence of periapical abscesses in patients treated with GCs was 1.5% compared to 0.39% in patients who were not treated with GCs. The OR for periapical abscesses in patients treated with GCs was 2.53 compared with OR of 0.66 in patients not treated with GCs. The differences were statistically significant (p < .0001). The prevalence of periapical abscesses in patients with SLE was 1.88%. The OR was 3.18 and the difference statistically significant (p < .0001). Conclusions: Under the conditions of this study, it appears that the prevalence of periapical abscesses is higher in patients with SLE. Patients receiving GCs therapy, either for SLE or for other conditions, may present higher prevalence of periapical abscesses